Leadership and Apparatus Competence on Village Fund Accountability: The Mediating Role of Technology Utilization in Jayapura City - Abner Kambu; Yohanis Rante; Westim Ratang; Jack H Syauta (West Science Journal Economic and Entrepreneurship, 2026)
This study analyzes the effect of village head leadership and apparatus competence on the accountability of village fund management, with technology utilization as a mediating variable, in the customary villages (kampung adat) of Jayapura City, Papua, Indonesia. The study is motivated by the rising allocation of village funds, which has not been matched by a commensurate level of accountability, as indicated by a report from the Indonesian Financial and Development Supervisory Agency (BPKP, 2022) and several cases of fund misuse in Jayapura City. A quantitative approach with an explanatory research design was employed. The sample consisted of 100 respondents drawn from 10 customary villages, each represented by 10 respondents (village head, treasurer, secretary, bamuskamp, technical implementers, and community members). Data were collected through a five-point Likert-scale questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM) in SmartPLS with a bootstrapping procedure of 3,000 resamples. The results show that village head leadership and apparatus competence have a positive and significant effect on both technology utilization and the accountability of village fund management. Technology utilization positively affects accountability. Technology utilization also positively and significantly mediates the effects of leadership and apparatus competence on accountability, with variance accounted for (VAF) values of 36.8% and 37.2%, respectively, indicating partial mediation. The model explains 70.7% of the variance in village fund management accountability. These findings underscore the importance of synergy among leadership, competence, and digitalization in strengthening public-sector financial accountability at the village level, particularly in culturally distinctive regions such as Papua.